1984
DOI: 10.1063/1.94818
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved observation of carrier leakage in 1.3-μm In1−xGaxAsyP1−y lasers

Abstract: Articles you may be interested inSuppression of electron and hole leakage in 1.3 μm AlGaInAs/InP quantum well lasers using multiquantum barrier Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This quaternary layer has a different composition from the active region and the recombination emission caused by carrier leakage (λ=1.05µm) was optically detected. Experimental results [42,43,44,45,46] showed that significant electron leakage can occur in InGaAsP/InP double heterostructures constituting one of the mechanisms of sublinearity of the light-current characteristics and also of the temperature dependence of the threshold current in laser diodes. The method of spectrally resolved luminescence was used to study heterobarrier carrier leakage in CMBH lattice matched and compressively strained 1.3 µm InGaAsP/InP lasers with an active layer of the order of 1 µm in width [44].…”
Section: Optical Technique Of Studying the Carrier Leakagementioning
confidence: 99%
See 1 more Smart Citation
“…This quaternary layer has a different composition from the active region and the recombination emission caused by carrier leakage (λ=1.05µm) was optically detected. Experimental results [42,43,44,45,46] showed that significant electron leakage can occur in InGaAsP/InP double heterostructures constituting one of the mechanisms of sublinearity of the light-current characteristics and also of the temperature dependence of the threshold current in laser diodes. The method of spectrally resolved luminescence was used to study heterobarrier carrier leakage in CMBH lattice matched and compressively strained 1.3 µm InGaAsP/InP lasers with an active layer of the order of 1 µm in width [44].…”
Section: Optical Technique Of Studying the Carrier Leakagementioning
confidence: 99%
“…The obvious method of studying the efficiency of carrier leakage under different conditions is to register the light resulting from recombination of carriers outside the active region [42,43,44,45,46]. Electro-luminescence image of InGaAsP/InP CMBH laser at 100mA forward bias, recorded by E. J. Flynn and D. A. Ackerman is shown in Fig.…”
Section: Optical Technique Of Studying the Carrier Leakagementioning
confidence: 99%